Daniel Varoujan by Paruyr Sevak - Gabrielyan, Vazgen (Bulletin of Yerevan University B: Philology, 2025)
The scientific interests of the great Armenian poet and literary critic (Doctor of Philology) Paruyr Sevak, starting from his student years, have encompassed a wide variety of writers from the Armenian Middle Ages to early modern and modern periods to contemporary writers, as well as theoretical issues of interest to modern literary criticism. This article focuses on Sevak's interpretation and appreciation of the poetry of the great Armenian poet Daniel Varoujan, which began in his student years and continued in the later years of his life.The article examines Sevak's consideration of Varoujan's work in different years, in particular Sevak's an extensive study of "Varujan's Poetry" in February of 1945. The aim of the article is to show that this study is truly a serious and well-structured literary research--with problem formulation, arguments and conclusions, and an original and new word of Varoujan studies of its time (why not also future studies).
Keywords: poetry; poetic series; Daniel Varoujan; homeland and patriotism; the national and the global; the what and the how; divided self and dilemma; the ideal and the reality